PENGARUH TINDAKAN RESTRAINT TERHADAP SKOR RUFA PADA PASIEN DENGAN PERILAKU KEKERASAN - Putri, Dwi Septiani; Elita, Veny; Indriati, Ganis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Violence behavior is one of mental disorders which can hurt oneself, others, and the environment. Patients withviolence behavior are treated in intensive room, categorized according to the condition called the RUFA score. TheRUFA score is to divided into intensive 1, intensive 2, and intensive 3. One of the intensive treatments to the patients isrestraint. This study aimed to find out the effect of restraint on RUFA score on patient with violent behavior in MentalHospital of Tampan Riau Province by applying pre-experiment research design and one group pretest posttest withoutcontrol group. The sample was 17 respondents who had experience on violent behavior and restraint. Accidentalsampling technique to used to determine the sample. The instrument used to collect the data was observation sheet.Univariate analysis to utilized to know the distribution of characteristic respondent and bivariate analysis to applied byusing wilcoxon test. The statistical test result found that there was change in RUFA score seen from the median beforerestraint 6 and the median after restraint 5. The statistical test showed that effect of restraint on the RUFA score of thepatient with violent behavior with p value (0.000) <α (0.05). Based on the results of this study to expected nurses canprovide services needed by patients who are to attached restraint.Keywords : restraint, RUFA score, violent behavior